Preoperative Anemia and Iron Deficiency Screening, Evaluation and Management: Barrier Identification and Implementation Strategy Mapping - Delaforce, Alana (J Multidiscip Healthc, 2020)
INTRODUCTION AND AIMS: Patients undergoing major surgery risk significant blood loss and transfusion, which increases substantially if they have pre-existing anemia. Preoperative Anemia and Iron Deficiency Screening, Evaluation and Management Pathways (PAIDSEM-P) outline recommended blood tests and treatment to optimize patients before surgery. Documented success using PAIDSEM-P to reduce transfusions and improve patient outcomes exists, but the reporting quality of such studies is suboptimal. It remains unclear what implementation strategies best support the implementation of PAIDSEM-P. METHOD: Maximum variation, purposive sampling was used to recruit a total of 15 participants, including a range of health professionals and patients for semi-structured interviews. Data analysis utilized a deductive approach informed by the Consolidated Framework for Implementation Research (CFIR) for barrier identification and the Expert Recommendations for Implementing Change (ERIC) for reporting recommended implementation strategies. A modified version of the Action, Actor, Context, Target and Time (AACTT) framework assisted with conceptualisation and targeted strategy selection. RESULTS: The analysis revealed five barriers: access to knowledge and information, patient needs and resources, knowledge and beliefs about the intervention, available resources, and networks and communications, which had strong ERIC recommendations, including conduct educational meetings, develop educational materials, distribute educational materials, obtain and use patients/consumers family feedback, involve patients/consumers/family members, conduct a local needs assessment, access new funding, promote network weaving, and organize clinician implementation team meetings. CONCLUSIONS: Mapping the barriers and strategies using the ERIC framework on the basis of individual actor categories proved to be useful in identifying a pragmatic number of implementation strategies that may help in supporting the utilisation of the PAIDSEM-P and other evidence-based healthcare implementation problems more broadly.